How Does Minimally Invasive Transforaminal Lumbar Interbody Fusion Influence Lumbar Radiologic Parameters? - Pereira, Cláudia (2019)
Abstract BACKGROUND: Minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) has become a popular method of interbody fusion. Clinical outcomes after single-level MIS-TLIF have been reported, but few studies have focused on the radiologic changes in the segmental parameters of the operated and adjacent segments and in lumbar lordosis. METHODS: From March 2009 to September 2016, 117 patients who underwent a single-level MIS-TLIF surgery for lumbar degenerative disease were enrolled in this retrospective study. The anterior disc height (ADH), posterior disc height (PDH), and segmental angle (SA) of the operated and adjacent levels and lumbar lordosis (LL) were evaluated on radiographs obtained pre- and postoperatively at 6- to 12-month follow-up visits. Cage-related parameters including fusion and subsidence rates were analyzed on postoperative computed tomography scans. Clinical assessment used validated outcome scores such as the Oswestry Disability Index questionnaire and the Odom criteria. RESULTS: ADH and PDH of the operated segment increased significantly after surgery, but no significant changes were seen in the SA of that level. Statistically significant decreases were observed in the PDH of both adjacent segments and increases in the adjacent superior SA. LL showed a slight but statistically significant improvement after surgery that was mostly correlated with a postoperative increase in the adjacent superior SA (r = 0.58; P < 0.001). No significant correlations were found between clinical and radiologic results. CONCLUSIONS: Single-level MIS-TLIF increased disc height but not the SA at the operated level. LL improvement after surgery was mainly associated with the increase of the cranial segmental angle